Financial Fragility and Central Bank: Are Minsky's Crisis and Austrian Business Cycle are Complementary? - Facchini, François (Journal of Reviews on Global Economics, 2015)
This article explains why Minsky's post-keynesian explanation tells only one side of the crisis' story. Indeed, the financial fragility of markets explains mainly the activity of Central bank i.e. the lender of last resort which increases the moral hazard phenomena and the socialization of risks. The regulated capitalism is, in this perspective, the cause of market instability and financial fragility. Indeed, moral hazard encourages commercial banks to take risks. In that respect, the economic policies implemented to manage the crisis of 2008 are inadequate.